Analisis Proses Manufaktur Checking Fixture untuk Pengecekan Bracket Brake Tube: Desain Gambar Checking Fixture Bracket Brake Tube - Listyantaka, Agnes; Kurniawan, Yani (Journal of Applied Mechanical Technology, 2023)
Analyze the checking fixture manufacturing process as an inspection tool for brake tube bracket parts according to the demands given and test its effectiveness. This research is a means to explore the field of manufacturing, especially in the manufacture of a checking fixture. Analysis of the quality of this checking fixture can increase cost efficiency in the production process and increase resource flexibility, namely by speeding up the process of checking brake tube bracket components. The datum location in this final project research is at the center hole of the base plate with a size of Ø 8 mm by looking at the datum coordinates on the 3D part, namely:” L:1152.00 W:-125.00 H:1635.00.”The data used in this final project research include: data on the results of coordinate measurements using Faro Portable Measurement Arm, data on the manufacturing process of Checking Fixture Bracket Brake Tube, data on the cost of making Checking Fixture Bracket Brake Tube. The initial stage of designing the checking fixtures (CF) Bracket Brake Tube design is obtained identification data for making initial concepts and design plans that are made and presented in a check sheet according to the design of the part to be made checking fixtures (CF). The design concept that has been made will be checked, if it is as desired then the overall design will be made for checking fixtures (CF) Bracket Brake Tube.”Inspection results on Checking Fixture Bracket Brake Tube using Faro Portable Measurement Arm show the results of "OK" with a value below the tolerance number, namely: ±0.15 mm for circle points and ±0.20 mm for surface points.”The Brake Tube Bracket Fixture Checking Manufacturing Process requires a total time of 65404 seconds or equal to 18.17 hours. The total estimated cost required in the manufacture of Checking Fixture Bracket Brake Tube, amounting to:” IDR 9,114,774.9